(untitled) (Filološke studije, 2019)
I discuss varieties of ethical generalities that appear in the area between strict moral generalism and radical particularism. Arguments in support for particularism are presented, especially in relation to the question what kinds of generalities moral particularism may allow for. I discuss R. Audi’s model of moderate particularism that preserves prima facie duties, all in putting them into a complex normative and deliberative structure that is supposed to be «holism friendly». Next, M. Little and M. Lance version of particularism building upon defeasible principles is presented. J. Dancy’s particularism and his idea of a default reason are then discussed. I propose that interpreting prima facie duties in terms of tendencies may help to understand the status and workings of ethical generalities consistent with particularism.